1978
DOI: 10.1111/j.1348-0421.1978.tb00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible Citrate‐Utilizing Ability in Escherichia coli Isolated from Pigeons, Pigs and Cattle

Abstract: Isolation of citrate-utilizing variants of Escherichia coli has been demonstrated (5), but no genetic study of citrate-utilizing ability (Cit+) has been reported. This paper deals with isolation of Cit+ E. coli strains from pigeons, pigs and cattle, and the instability and transferability of citrate-utilizing ability in the strains, indicating that the ability is controlled by a plasmid.Thirteen of 36 strains of E. coli isolated from cloacal swabs of 22 pigeons in a pigeonry in Sapporo, Hokkaido, grew on Simmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 4 publications
0
25
0
1
Order By: Relevance
“…The citrate-fermenting ability of these gram-negative bacteria appears to be linked to the presence of genetically unstable determinants such as plasmids (13,14,18,32,33,37,38) (12,36,41), the energetics of citrate uptake are not yet understood. Kempler and McKay (19) demonstrated that the ability to transport citrate was linked to a 7.9-kilobase (kb) plasmid that appears to be present in all citrate-fermenting L. lactis strains analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The citrate-fermenting ability of these gram-negative bacteria appears to be linked to the presence of genetically unstable determinants such as plasmids (13,14,18,32,33,37,38) (12,36,41), the energetics of citrate uptake are not yet understood. Kempler and McKay (19) demonstrated that the ability to transport citrate was linked to a 7.9-kilobase (kb) plasmid that appears to be present in all citrate-fermenting L. lactis strains analyzed.…”
mentioning
confidence: 99%
“…The citrate-fermenting ability of these gram-negative bacteria appears to be linked to the presence of genetically unstable determinants such as plasmids (13,14,18,32,33,37,38) or transposons (15). The presence of plasmid-or transposonencoded citrate transport systems enables members of the Enterobacteriaceae to utilize citrate as the sole carbon source.…”
mentioning
confidence: 99%
“…The Cit character and drug resistance markers of R plasmids were co-transmitted by conjugation in many transconjugants tested. But, since transconjugants carrying only the citrate-utilizing determinant were found during transfer experiments except in some of the human isolates (Table 6), it can be concluded that the Cit character, like those for an H2S-positive E. coli strain, is located on a transmissible plasmid (Cit plasmid) which differs from R plasmid, as described by Sato et al (1978) …”
Section: Discussionmentioning
confidence: 99%
“…They were obtained by direct cultivation, using MacConkey agar (Eiken) plates, and identified as E. coli by 34 biochemical tests (Ishiguro, Oka & Sato, 1978).…”
Section: E Coli Strains Examinedmentioning
confidence: 99%